The Response Time of Trauma and non Trauma Patients Handling in Emergency Room Surabaya - Yuani Setiawati; Maya Hapsari Kusumaningtyas; Annete d’Arqom (UNUSA Press, 2022)
Background: Emergency room is one of the unit services in hospitals that provide first services in patients with threat of disability or even death. Emergency room is a service unit in hospital with 24 service hours for 7 days in a week. The high risk and working hours in the emergency room requires the medical personnel that have a good response times in triage room. Objective: To compare response time of medical personnel when handling trauma and non trauma patients in the emergency room. Method: A non-experimental, quantitative research methods using analytic observational. The population of this study was patient in emergency room Soetomo hospital Surabaya. The amount of the sample was 244 which divided into 41 trauma case and 203 non trauma case. Result: Response time of patients with trauma injuries that include quick category (< 5 minutes) amounted to 35 patients and 6 patients in slow category (> 5 minutes) with average response times of trauma patients is 6.244 minutes. Response time of patients with non trauma injuries that include quick category (< 5 minutes) amounted to 161 patients and 42 patients in slow category (>5 minutes) with average response times of non trauma patients is 3.722 minutes. The p value response times of medical personnel in dealing with trauma and non-trauma patients is 0.374 (> 0.05) which means there is no difference in response times from medical personnel in handling trauma and non-trauma patients. Conclusion: There was no difference in the response time of medical personnel in trauma and non-traumatic patients handling (p>0,05). Overall, it was found that the average emergency room’s response time at Soetomo hospital was 4.15 minutes, still meeting the applicable standards.